Kepemimpinan Perempuan dalam Meningkatkan Kinerga Organisasi pada KOPRI (Korps PMII Putri) Wilayah Lampung - Siti Wuriyan (International Journal of Publication Unit (IUJP) Agus Salim Metro, 2019)
ABSTRACT Leadership is the power of leaders to invite, influence, and move others to do something, in order to achieve effective and efficient goals in an organization. KOPRI is short for Putri PMII Corps, which is part of the PMII organization which is semi-autonomous, with the meaning